Analisis Dualitas Struktur-Agensi: Potret Manusia Silver Dalam Lanskap Sosial Urban Jakarta - Launa .; Bambang Mudjiyanto; Fit Yanuar; Nursyamsi .; Hayu Lusianawati (CV. ITTC INDONESIA, 2025)
This study presents a phenomenological portrait of the ‘Silver Man’ within Jakarta's urban social landscape using Anthony Giddens’s structuration analysis framework. Silver Man, as social actors in public space, inherently embodies the duality of structure and agency. This research explores how social structures—such as urban political-economic conditions, stigma, and public norms—simultaneously shape and are shaped by the agency of individual Silver Man individuals. Through thematic analysis of everyday practices and subjective experiences, it is found that they are not merely passive objects of structural pressures (poverty, the need for survival), but also active agents who reflexively negotiate these conditions. Their agency is evident in their adaptation strategies, expressions of unique identities, and reconfigurations of the meaning of social space. The results underscore the dialectical nature between the available ‘rules and resources’ (structure) and the ‘social practices’ (agency) they engage in, demonstrating that structure and agency are interconnected and inseparable in shaping the social reality of Silver Man. This study provides a richer understanding of the city's urban social dynamics and contributes to structuration theory in explaining the complexity of marginalization amidst Jakarta's modernizing urban space.